THE CORRELATION BETWEEN FAMILY SUPPORT AND CONTROLLING HIGH BLOOD PRESSURE IN HYPERTENSION PATIENTS AT THE BAKAUHENI INPATIENT HEALTH CENTER IN 2022 - Ni Wayan Desi Ayu Djuwita; Simamora, Rotua Suriany; Anggraini, Ani (Rena Cipta Mandiri, 2024)
Hypertension is one of the non-communicable diseases and is commonly known as the silent killer. If hypertension is not treated it can lead to complications up to death. In order for people with hypertension to keep their blood pressure stable, so it is necessary to control high blood pressure in people with hypertension. Family support is one of the most influential factors in controlling high blood pressure. Research Objectives To determine the relationship between family support and high blood pressure control in hypertension sufferers at the Bakauheni Inpatient Health Center in 2022. Research Methods The methods used by researchers are quantitative. The design in this study used Observational Analytics and used a Cross Sectional approach. The sample of this study was hypertension sufferers at the Bakauheni Inpatient Health Center, as many as 75 respondents. The sampling technique in this study used probability techniques and used a type of simple random sampling. Bivariate analysis using Chi Square statistical test. Research Results The Following p-value were obtained (0.000) < (0.05). This shows that Ho was rejected and Ha was accepted. Obtained from bivariate results that showed that 58 respondents (77.3%) had family support in the good category, where respondents with high blood pressure control in the good category were 49 respondents (65.3%). Conclusion Based on the results of the study, there is a significant relationship between family support and high blood pressure control in hypertension sufferers at the Bakauheni Inpatient Health Center in 2022.